2022
DOI: 10.5430/wjel.v12n2p82
|View full text |Cite
|
Sign up to set email alerts
|

Online Education and Assessment: Profiling EFL Teachers' Competency in Saudi Arabia

Abstract: The expanding digital era, emerging geopolitical dynamics, and the birth of the new ‘normal’ that the world has witnessed in the recent times have made the urgency of revamping the academic arena obvious to all. These developments have also made it essential for teachers to be technologically and pedagogically ready to cater to individual needs by being adaptive. This calls for identification of gaps between current pedagogical practices and best practices for the new age classrooms based on the premise that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The study reported high competency level, high level of integration technology in teaching and high level of using online assessment. It also found that the only significant difference was in teachers' integration of technology, which varied by gender [39]. Accordingly, this study also focuses on question 2: Is there any difference in the need for professional competencies regarding gender, school type, years of teaching experience, school levels and school locations?…”
Section: Introductionmentioning
confidence: 91%
“…The study reported high competency level, high level of integration technology in teaching and high level of using online assessment. It also found that the only significant difference was in teachers' integration of technology, which varied by gender [39]. Accordingly, this study also focuses on question 2: Is there any difference in the need for professional competencies regarding gender, school type, years of teaching experience, school levels and school locations?…”
Section: Introductionmentioning
confidence: 91%
“…Gender was the only significant difference found in teachers' use of technology. Recommendations include adapting to the emerging needs of digital learners and staying abreast of new technologies [29].…”
Section: Best Practices For Online Teaching and Learningmentioning
confidence: 99%
“…Effective and professional teaching should be the norm in the classroom. To ensure satisfactory learning, the accomplishment of learning objectives, as well as the genuine and accurate assessment of learning, it is necessary for them to possess a thorough understanding of the subject, to be made aware of the usage of practical learning approaches and strategies, and to use many tools competently and effectively (Abdullah, 2022). However, research has confirmed that teachers' assessment abilities and capabilities are lacking (Rural, 2021).…”
Section: Introductionmentioning
confidence: 99%